Studi Komparasi antara Tes Testlet dan Uraian dalam Mengukur Hasil Belajar Kognitif Siswa Kelas XI SMA Negeri 1 Gombong - Murti, Murti; Wiyanto, Wiyanto; Hartono, Hartono (UPEJ Unnes Physics Education Journal, 2018)
The purpose of the research is to find out does the testlet test can work as a essay test. This research is an explorative research done to investigate a relatively new phenomenon. In accordance with the research itself, research design used is the One Group Posttest Only Design. Sample is don randomly (Random Sampling). The research is done in SMA Negeri 1 Gombong with the subject of the study is the students of XI MIPA 4 and XI MIPA 6. Based on the research’s result with the t-test analysis, showed that t-value= 1.85 for the XI MIPA 4 students and t-value= 1.89 for the XI MIPA 6 students, with t-table= 1.99. Therefore, from both of the research sample classes, the t-value is lesser that the t-table, so the conclusion is that there is no difference in the students’ cognitive learning outcome evaluated using testlet test and essay test, so testlet test can work as essay test.